Freeze-resistant wearable strain sensors based on hyperbranched cellulose nanofiber hydrogels - Houhuang Tao; Xue Yu; Lanqing Li; Maria De Los Angeles; Na Wang (Results in Engineering)
Hydrogel sensors are becoming increasingly important for electronic devices because of their flexibility, versatility, and high sensitivity, especially in applications that necessitate compatibility with human skin. However, creating hydrogel sensors that maintain high toughness and antifreeze properties in extreme cold conditions continues to be a challenge. This study introduces phytic acid (PA) into a hyperbranched polyamide (HBP)/cellulose nanofiber (CNF) interacting network to develop a freezing-resistant, high-toughness hydrogel with sustained electrical conductivity (HBP/CNF-PA). The terminal amino groups of the HBP enhance hydrogen bonding, thereby improving the mechanical strength and conductivity of the hydrogel. The resulting HBP/CNF-PA hydrogels exhibit a tensile strength of 219.7 kPa, a compressive strength of 0.87 MPa, and dissipate energy at a rate of 795 kJ·m-3, along with a conductivity of 0.45 S·cm-1 and exceptional frost resistance, extending down to -40°°C, due to the ionization induced by PA. Hydrogels were utilized to create flexible sensors with a sensitivity of up to 1.34 V·g-1. The sensors detect signals with a time interval of just 197 ms and 215 ms, capable of identifying changes in relative resistance caused by wrist flexion, gestures, and voice movements.